Differential Expression of the Tetraspanin CD9 in Normal and Leukemic Stem Cells - Lahlil, Rachid; Scrofani, Maurice; Aries, Anne; Hénon, Philippe; Drénou, Bernard (Biology (Basel, Switzerland), 2021)
CD9 plays a crucial role in cellular growth, mobility, and signal transduction, as well as in hematological malignancy. In myeloid neoplasms, CD9 is involved in the altered interactions between leukemic and stromal cells. However, apart from its role in CD34+ progenitors and myeloid and megakaryocytic differentiation, its function in normal and leukemic pluripotent cells has not yet been determined. Very small embryonic-like stem cells (VSELs) are promising pluripotent stem cells found in adult tissues that can be developed for safe and efficient regenerative medicine. VSELs express different surface receptors of the highest importance in cell functioning, including CD9, and can be effectively mobilized after organ injury or in leukemic patients. In the present study, we observed that CD9 is among the most expressed receptors in VSELs under steady-state conditions; however, once the VSELs are expanded, CD9+ VSELs decrease and are more apoptotic. CD9– VSELs had no proliferative improvement in vitro compared to those that were CD9+. Interestingly, the addition of SDF-1 induced CD9 expression on the surface of VSELs, as observed by flow cytometry, and improved their migration. In addition, we observed, in the phenotypically identical VSELs present in the peripheral blood of patients with myeloproliferative neoplasms, compared to healthy subjects, a significantly higher number of CD9+ cells. However, in their hematopoietic stem cell (HSC) counterparts, the expression remained comparable. These results indicate that, likewise, in progenitors and mature cells, CD9 may play an important function in normal and malignant VSELs. This could explain the refractoriness observed by some groups of expanded stem cells to repairing efficiently damaged tissue when used as a source in cell therapies. Understanding the function of the CD9 receptor in normal and malignant CD34+ and VSELs, along with its relationship with the CXCR4/SDF-1 pathway, will enable advances in the field of adult pluripotent cell usage in regenerative medicine and in their role in leukemia.